The Field-Frequency Lock for Fast Field Cycling Magnetic Resonance: From NMR to MRI - Galuppini, G.; Magni, L.; Ferrante, G. (Frontiers in Physics, 2021)
Magnetic field stability plays a fundamental role in Nuclear Magnetic Resonance (NMR) and Magnetic Resonance Imaging (MRI) experiments, guaranteeing accuracy and reproducibility of results. While high levels of stabilisation can be achieved for standard NMR techniques, this task becomes particularly challenging for Fast Field Cycling (FFC) NMR and MRI, where the main magnetic field is switched to higher or lower levels during the pulse sequence, and field stabilisation must be guaranteed within a very short time after switching. Recent works have addressed the problem with rigorous tools from control system theory, proposing a model based approach for the synthesis of magnetic field controllers for FFC-NMR. While an experimental proof of concept has underlined the correctness of the approach for a complete FFC-NMR setup, the application of the novel, model based Field-Frequency Lock (FFL) system to a FFC-MRI scanner requires proper handling of field encoding gradients. Furthermore, the proof of concept work has also stressed how further advances in the hardware and firmware could improve the overall performances of the magnetic field control loop. The main aim of this perspective paper is then discussing the key challenges that arise in the development of the FFL system suitable for a complete MRI scanner, as well as defining possible research directions by means of preliminary, simulated experiments, with the final goal of favouring the development of a novel, model based FFL system for FFC-MRI.